Microstructure characteristics of Wufeng-Longmaxi shale gas reservoirs with different depth, southeastern Sichuan Basin - Weixin LIU; Longfei LU; Zhihong WEI; Lingjie YU; Wentao ZHANG; Chenjie XU; Deliao YE; Baojian SHEN; Ming FAN (Shiyou shiyan dizhi, 2020)
Thin section analysis, X-ray diffraction, conventional scanning electron microscopy (SEM), high-resolution Ar+ ion polishing SEM, mercury intrusion, nitrogen adsorption, total organic carbon (TOC) content and porosity analyses were used to determine the mineral composition, microstructure and micro-pore volume of shale reservoirs from different depths in the Upper Ordovician Wufeng Formation and Lower Silurian Longmaxi Formation in southeastern Sichuan Basin. There are slight differences in the content of siliceous, clay, carbonate and other minerals in shale reservoirs of well D1 in the deep layer and well J1 in the shallow layer, and the longitudinal changes are similar. Only high-quality shale layers with a silica content greater than 40% have different thicknesses. The shale reservoirs of the Wufeng-Longmaxi formations in the deep and shallow layers are dominated by micro-pores in organic matter disseminated in the shale matrix, and the microfractures around the boundaries of silt particles or organic grains and micro-foliation seams parallel to bedding plane are also common, while and intergranular pores are not developed. The high quality shale reservoir at the bottom is structurally isotropic, and the vertical and horizontal structural anisotropy becomes stronger upwards, with thinner micro-lamina and more foliation seams. The TOC content is high at the bottom, and diminishes upwards. The porosity at the bottom shows the same changing trend, indicating a large contribution of organic pores; however, the decrease in porosity is significantly smaller than that of TOC, which is inferred to be related to the existence of more inorganic pores in the shale. The mineral composition, microstructure, TOC and porosity of the Wufeng-Longmaxi shales in the deep and shallow layers have similar changes with depth. Compared with well J1 in the shallow layer, the high-quality reservoir in well D1 in the deep layer has a larger number of micro-pores, meso-pores, macro-pores and total pore volume, which might be explained by more inorganic pores such as grain boundary pores.The shale reservoirs of the Wufeng-Longmaxi formations in the southeastern Sichuan Basin maintain a good porosity under deep burial conditions and have good storage space.